Autorregulación y la publicidad sexista: Oportunidad de mejora para el CONAR - Sosa, Alex (Pontificia Universidad Católica del Perú, 2018)
In this article, the author develops the problem ofs exist advertising and he sets out self-regulation as an alternative to sanction it. Along these lines, he introduces CONAR as an institution responsible for self-regulation within advertising, and he highlights the issuance of an objective criterion for evaluation and eventual sanction of sexist advertising, this within the framework of the validity of its Advertising Code of Ethics 2007, but after a series of modifications to regulatory framework, the author criticizes its lack of application, and he culminates affirming the advantages of an advertising self-regulation, represented through CONAR.

En el presente artículo, el autor desarrolla la problemática de la publicidad sexista y plantea la autorregulación como una alternativa para sancionarla. En esa línea, introduce al CONAR como una institución encargada de la autorregulación dentro de la publicidad, y destaca la emisión de un criterio objetivo para la evaluación y eventual sanción de la publicidad sexista, esto en el marco de la vigencia de su Código de Ética Publicitaria del 2007, pero luego de una serie de modificaciones al marco regulatorio, el autor crítica su falta de aplicación, y culmina afirmando las ventajas de una autorregulación publicitaria, representada a través del CONAR.
Self-regulation and sexist advertising: Opportunity for improvement for CONAR
Keywords: Publicidad; https://purl.org/pe-repo/ocde/ford#5.05.00